Scalable Management Architecture for Electronic Health Records Based on Blockchain - Kaschel-Carcamo, H (Institute of Electrical and Electronics Engineers Inc., 2022)
The rise of communication and information technology in conjunction with the health emergency due to COVID-19 has accelerated the implementation of electronic health records (EHR). These registries are constantly growing and put people s privacy, information security and health data at risk. The use of the blockchain is shown as an alternative for the distribution and management of health data. However, the blockchain has limitations of scalability and interoperability. This work proposes a scalable management architecture based on blockchain that will be analyzed by comparing it with other works reviewed in the document. The model proposed in three modules aims to deliver an alternative to EHR s scalable management solution based on the private blockchain such as Hyperledger Fabric. © 2022 IEEE.